Evaluation and concept of building performance towards sustainability in Malaysia higher institutions / Natasha Khalil, Husrul Nizam Husin and Abdul Hadi Nawawi - Khalil, Natasha; Husin, Husrul Nizam; Nawawi, Abdul Hadi (Universiti Teknologi MARA Cawangan Selangor, 2018)
Abstract The growing populations of students to higher institution is increasing year by year, therefore, it is importance to ensure that the building is well functioned throughout its lifecycle. Inevitably, the educational process may be interrupted if the building experience a poor performance conditions, thus affect the students’ academic achievement. Many studies have proved that there is the significance in providing holistic performance in educational buildings that able to improve the students’ learning environment. 7his study is aimed to provide a new rating tool of building performance that is hoped to be used for Malaysia’s higher educational buildings towards students’ learning improvement.